PENGGUNAAN MEMBRAN POLY(LACTIC-CO-GLYCOLIC) ACID (PLGA) YANG DIPERKUAT OLEH NANOSELULOSA UNTUK PROSEDUR GUIDED BONE REGENERATION (GBR) - Kurniawati, Nathasya; Rakhmatia, Yunia Dwi; Damayanti, Lisda (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Introduction: Poly (lactic-co-glycolic acid) (PLGA) was developed as a bone regeneration membrane due to its biocompatibility and biodegradability, despite its inherent lack of mechanical strength. One method of enhancing the mechanical strength of PLGA is through its combination with nanocellulose, which possesses high mechanical strength. Nevertheless, nanocellulose exhibits rigidity that renders it challenging to manage in a clinical setting. Aim: The objective of this study was to ascertain the potential of PLGA membranes reinforced by nanocellulose as a bone regeneration material. Method: A review of the literature was conducted through online databases PubMed, Science Direct, SCOPUS, and MDPI for the past 10 years. Result: The results of the search yielded four articles discussing the use of synthetic polymers, particularly PLGA reinforced by nanocellulose as a membrane. Of the four articles identified, two solely addressed the biological properties of the membrane, one solely the mechanical properties, and one reported both. The articles found support the theory regarding the advantages and disadvantages of PLGA and nanocellulose as membranes. Conclusion: The utilisation of PLGA membranes reinforced by nanocellulose merits further investigation, as these membranes demonstrate the potential to satisfy the design criteria for a mechanical barrier membrane in bone regeneration.